The acidity of wood and panel product was important factor to impact on metal corrosion and give effect on adhesive curing time. The objective of this research was to explore of pH and buffering capacity from nine tropical woods. Method to determination of pH and buffering capacity reffers to Johns and Niazi (1980) experiment. The result of this research showed that nine tropical woods which observed had different acidity and buffering capacity. The range of wood acidity had pH 4-7. The cor - Apri Heri ISWANTO; Tito SUCIPTO; Fauzi FEBRIANTO (Departemen Hasil Hutan, IPB, 2011)
The acidity of wood and panel product was important factor to impact on metal corrosion and give effect on adhesive curing time. The objective of this research was to explore of pH and buffering capacity from nine tropical woods. Method to determination of pH and buffering capacity reffers to Johns and Niazi (1980) experiment. The result of this research showed that nine tropical woods which observed had different acidity and buffering capacity. The range of wood acidity had pH 4-7. The correlation value of pH and buffering capacity from this research about 4-5 for base and acid buffering. Keywords: acidity of wood, pH, buffering capacity.